The Difference In Meaning Of “Flirting” In The Gender Mirror (Women And Men) - Elizabeth Sitio; Supraini Siagian; Rachel M. Sihombing; Maria Cinta Br Manullang; Vivi Sitinjak (Jurnal Dieksis ID, 2026)
The urgency of this study lies in examining the gendered differences in the meaning of “flirting,” revealing how social norms and gender identity shape interpretation, with implications for linguistic and discourse analysis. Flirting is a common yet complex form of interpersonal communication that functions as a socially and linguistically mediated act. Although it is often treated as a universal behavior, previous studies demonstrate that the meaning and interpretation of flirting differ significantly across genders. His study aims to examine differences in the meaning of ‘flirting’ between men and women by positioning flirting as a speech act shaped by gender performativity, social context, and linguistic ambiguity. This study employs a qualitative descriptive approach using discourse analysis to explore how meaning is constructed in interaction. Data sources include prior empirical journal articles and discourse examples from both offline and online communication contexts. Data were collected through documentation and systematically selected based on relevance to the research focus. The analysis involved data reduction, categorization of linguistic features, and contextual interpretation. To ensure trustworthiness, the study applied theoretical triangulation, repeated close reading, and peer debriefing to enhance credibility and reduce researcher bias. The findings reveal that men tend to interpret flirting as an explicit signal of romantic or sexual interest, while women more frequently understand it as a form of friendliness, relational bonding, or playful interaction. This divergence highlights a gap between dominant theoretical explanations and real-life communicative practices. The study contributes to flirting research by emphasizing language as the central mechanism through which flirtation is produced, negotiated, and misinterpreted. It also proposes that ambiguity is not a weakness of flirting, but its defining feature, allowing participants to manage desire, politeness, and social risk simultaneously.